Does Socio-Economic Status Have Different Impact on Fluid and Crystallized Abilities? Comparing Scores on Raven’s Progressive Matrices, Kaufman Assessment Battery for Children II Story Completion and Kilifi Naming Test Among Children in Ghana - Anum, Adote (Frontiers in Psychology, 2022)
Current literature shows an association between intelligence and sociocultural or socioeconomic factors. The available evidence supports a stronger effect of exogenous factors on measures of crystalized intelligence than on fluid intelligence. Despite this, the sources of variability in fluid and crystalized intelligence have not been explored adequately in intelligence research. The purpose of this study was to compare performance on tests that measure fluid and crystallized intelligence among children selected from public and private schools in Ghana. We tested the assumption that SES will have a stronger effect on tests that measure crystallized intelligence than on fluid intelligence. We selected 185 children between 6 and 12 years from private and public schools and used inclusion in a private or public school as a proxy for SES. We administered the Raven’s Coloured Progressive Matrices (RCPM), a fluid intelligence test, the KABC II story completion subtest as a measure of inductive reasoning and crystallized intelligence and the Kilifi Naming Test, a verbal ability measure designed to minimize the effect of school on vocabulary. The results showed age-related improvement in scores on all three tests with effect sizes ranging from .42 to .52. We also found significant effect for type of school on all the tests with effect sizes ranging from .37 to .66. The results also showed an increasing disparity in performance on the tests favoring children selected from private schools. These suggest that fluid and crystalized intelligence are affected by socioeconomic factors. The results also showed that SES factors tend to affect crystallized ability more than it affects fluid ability. The results are discussed in the context of differences in socioeconomic resources available to children such as quality of education in low- and middle-income countries.